The analysis of domestic water demand and management in Duren Village, Bandungan, Semarang District - Suhendra Suhendra (BUMI: International Journal of Environmental Reviews, 2023)
The demands for and availability of water is one of the main natural factors that can sustain life and means of livelihood. Springs originating from the foot of Mount Ungaran are the main water sources for Duren Village, Bandungan District, Semarang, which play an important role in meeting domestic household water needs. In addition to analyzing various types of techniques and community involvement in managing water supply, this study aims to look at the needs and patterns of water use that are utilized. This research uses a survey method and is descriptive and analytical in nature through field observations and in-depth interviews with local residents using a questionnaire in the data collection process. Statistical analysis used for data analysis is analysis of frequency distribution tables and analysis of various correlations. Based on the study findings, the community views the availability of water as very high due to the abundance of water during the rainy season, the absence of drought during the dry season, and the ease of accessing water due to the direct supply of available water, except during the rainy season when mud or soil debris Landslides enter the water source so that the water becomes cloudy. Springs are used to supply the domestic needs of the population and the quality of the water at the study site is very good or clean. In addition, the results of the analysis at the research location show a very high level of community involvement in the protection and preservation of water sources. This indicates that Duren Village residents consistently participate in efforts to manage water sources by carrying out mutual cooperation activities, slametan traditions, and recitation traditions. However, because there is no specific organization or group that regulates or assists in the management of water sources to become more structured and organized for optimal use therefore the utilization rate of water sources is still below average.